Mentoring for well-being, engagement and academic achievement in higher education students - Gonçalves, Joana C.; Duarte, António M.; Marques-Pinto, Alexandra; Paulino, Paula; Figueira, Célia P.; Ferreira, Paula A.; Hagá, Sara; Barros, Alexandra; Pereira, Nádia S.; Da Luz, Rita A.; Amaral, André; Mesquita, Filipe (Frontiers in Education, 2025)
College students are recognized as a vulnerable population due to excessive academic demands, societal changes, and limited resources, leading to increased stress and burnout. Mentoring has been proposed as a strategy to enhance students skills and well-being. However, research on mentoring programs reveals a gap in addressing definitional, theoretical, and methodological issues. The aims of the present work were, therefore, to design and pilot a mentoring-based intervention to assist students transitioning to higher education, through an action-research and psychoeducational paradigm, and to address the aforementioned gaps. Two studies were conducted at a Portuguese public university’s department, between August of an academic semester and the following March. Study 1 involved designing and testing a training program to equip mentors with tools to support 1st year students’ well-being, engagement, and academic performance. A quasi-experimental one, and another inspired by a multiple-case experiment design, were implemented. The study included an experimental (n = 20) and control group (n = 15), through self-selection sampling, with pre- and post-test. The mentors’ knowledge was measured through a purposedly built questionnaire on vocational development, approaches to learning, self-regulated learning, sense of belonging, and socio-emotional skills. The experimental group’s participants also provided feedback on the perceived impact of the training program through 10 additional items at post-test. Study 2 examined the impact of this training through the effects of its implementation on a convenience sample of four mentees (1st year students), assessing their knowledge and skill perception on similar variables at pre- and post-test. Additional items and an open-ended questionnaire to evaluate the intervention’s perceived impact were also included. Quantitative data underwent statistical analysis (independent- and paired-samples t-test, except for “knowledge about approaches to learning,” analyzed through Mann–Whitney U and Wilcoxon signed-rank tests), and a case-by-case analysis, while qualitative data were subjected to thematic analysis. Results indicated a statistically significant knowledge increase in Study 1’s experimental group after training, contrasting with the control group, and a potentially positive impact on the development of Study 2’s mentees. The perceived changes’ analysis indicated that most participants experienced a moderate to satisfactory impact. The present work highlights the potential benefits of a mentoring intervention with a precedent mentors’ training program.